KONSTRUKSI MASKULINITAS LAKI-LAKI DALAM IKLAN EXTRA JOSS VERSI LAKI GO TO HEALTH - Nuky Prastya, I Kadek Sanjita; Sugiarica Joni, I Dewa Ayu; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2019)
ABSTRACT’; Advertisement is representing an activity to launch ideas and items using persuasive tricks. One of them is to create an ideal image for men in accordance with market demand through the appearance of a muscular body and handsome face. However, it’s different with Extra Joss Advertisement version called “laki go to health” which represent a different masculine image from the previous advertisement. Through qualitative research methods with the constructivisti paradigma ands semiotic analysisf of Rolando Barthesi, researchers found a different construction of man masculinity in Extra Joss ads called “laki go to health”. The changing masculinity in this advertisement is not only based on physical appearance, but is more than showing man lifestyle. This can be seen from changing regular and irregular lifestyles which are constructed fromaathe beginningito=the1end of the advertisementdand are increasingly confirmed by the man tagline called “laki go to health”. Keywords: Advertisement, Construction, Man, Masculinity, Semiotic.